How different online recruitment methods impact on recruitment rates for the web-based coortesnaweb project: a randomised trial - Cauane Blumenberg; Ana Maria Baptista Menezes; Helen Gonçalves; Maria Cecília Formoso Assunção; Fernando César Wehrmeister; Aluísio J. D. Barros (BMC Medical Research Methodology, 2019)
Abstract Background The number of web-based E-epidemiologic studies using online recruitment methods is increasing. However, the optimal online recruitment method in terms of maximizing recruitment rates is still unknown. Our aim was to compare the recruitment rates of three online recruitment methods and to describe how these rates differ according to individual’s socioeconomic and demographic factors. Methods A total of 2394 members of the 1993 Pelotas birth cohort that provided an e-mail address, a Facebook name, and a WhatsApp number during a face-to-face follow-up were randomly allocated to be recruited by e-mail, Facebook or WhatsApp (798 individuals per method). This was a parallel randomised trial applying a block randomisation (block size = 3). Between January and February 2018, we sent messages inviting them to register into the web-based coortesnaweb platform. Recruitment rates were calculated for each method, and stratified according to the individual’s socioeconomic and demographic characteristics. We also analysed absolute and relative inequalities on recruitment according to schooling and socioeconomic position. Results Out of the 2394 individuals analysed, 642 registered into the platform. The overall recruitment rate was 26.8%. Recruitment rates for women were almost 10 percentage points higher compared to men. Facebook was the most effective recruitment method, as 30.6% of those invited through the social network were recruited. Recruitment rates of e-mail and WhatsApp were similar (recruitment rate = 24.9%). E-mail and Facebook were the most effective recruitment methods to invite highly educated and wealthier individuals. However, sending e-mails to recruit individuals also reflected in the highest inequalities according to schooling and socioeconomic position. In contrast, the lowest inequalities according to socioeconomic position were observed using Facebook. Conclusions Facebook was the most effective online recruitment method, also achieving the most equitable sample in terms of schooling and socioeconomic position. The effectiveness of online recruitment methods depends on the characteristics of the sample. It is important to know the profile of the target sample in order to decide which online recruitment method to use. Trial registration Brazilian Registry of Clinical Trials, identifier: RBR-3dv7gc, retrospectively registered in 10 April 2018.